Evaluating the Effectiveness of STRONGkids in Identifying Nutritional Risk in Outpatients of Child Health Care Clinics - Wu, Li; Xiao, Haiyan; Bian, Shanshan; Li, Jiuling; Li, Haixin; Zhou, Yaqin; Ding, Xuejing (International Journal of Child Health and Nutrition, 2025)
Aim: To investigate the value of the STRONGkids tool for screening malnutrition risk among pediatric outpatients in China. Methods: This multicenter, cross-sectional, observational study included pediatric outpatients at the Maternity and Child Health Care Hospital in Changzhou, China, from March 2021 to March 2022. More specifically, we performed anthropometric assessments and screened pediatric patients under 2 years of age for nutritional risk using the STRONGkids tool. Results: The total number of samples assessed for malnutrition risk was 1,062, of which 81.4% (n = 865) were low risk, 16.4% (n = 174) were medium risk, and 2.2% (n = 23) were high risk. In terms of sex, 81.2% (n = 448) of all males included in the present study were classified as low risk, while 16.5% (n = 91) and 2.3% (n = 13) were medium and high risk, respectively. Furthermore, the sensitivity and specificity of STRONGkids were 0.906 and 0.837, respectively, and the AUC was 0.872 (p < 0.01). Conclusion: Although our findings failed to reveal any significant association between malnutrition risk and sex, malnutrition risk was significantly associated with age category and was more likely to occur within the first year of life. The STRONGkids tool demonstrated diagnostic efficacy in screening outpatient children for nutritional risk and could accurately identify children at risk of malnutrition. It promotes children's growth and development, reduces the risk of disease, and is beneficial to long-term health.